Evaluating the feeding preferences of West Nile virus mosquito vectors using bird-baited traps. Issue 1 (December 2016) - Victoriano Llopis, Isis; Tomassone, Laura; Grego, Elena; Serrano, Emmanuel; Mosca, Andrea; Vaschetti, Gabriella; Andrade, Daniela; Rossi, Luca
Abstract Background The total contact rates (TCRs) between mosquito vectors and their potential hosts have a serious impact on disease transmission dynamics.Culex pipiens (sensu stricto ) (s.s .) is considered the main vector of the West Nile Virus (WNV) in Europe and birds are the reservoir hosts. The results of our previous study showed that WNV seroreactors are significantly more prevalent among raptors compared to a range of other wild avian groups. The current study aims to assess the role of bird type (raptorvs others) and bird size on mosquito feeding preferences in a free-choice experiment using bird-baited traps. Methods From July to September 2014, a battery of six bird-baited traps was operated in twelve mosquito capture sessions. Eight bird species, belonging to five different orders, including raptors, were used. After each session, the trapped mosquitoes were collected and identified using standard keys. Two sets of independent generalized linear mixed models (GLMM) were used to assess mosquito vector feeding preferences (MFp) among different bird species and types. Results A total of 304 mosquitoes belonging to seven taxa were collected, C. pipiens being by far the most abundant (84.2 % of the total mosquito catch). MostC. pipiens were engorged (83.59 %). The selected model showed that 25.6 % of the observed variability of MFp is explained by the interaction between bird size and bird type, withC. pipiens preferring to feed on large birds, especially raptors. The proportion of engorged mosquitoes was 1.9-fold higher in large (22.88 %; range 0–42 %) than in medium-sized raptors (11.71 %; range 0–33 %), and was nearly the same in medium-sized (9.08 %; range 0–26 %) and large (8.5 %; 6–24 %) non-raptor species. Conclusion Culex pipiens showed an obvious preference for large raptors, which concurs with the higher seroprevalence to WNV in our previous study. The appreciable feeding byC. pipiens on large raptors makes them useful alternative sentinels to poultry for WNV surveillance. Thus, wildlife parks and rehabilitation centers can contribute to surveillance efforts to a greater extent.